An Evaluation of Pollution Flushing for Ben Beo Basin (Cat Ba Island, Hai Phong): Using the Estimation of Pollution Flushing - Thi Le Ha, Trinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 4, 2021)
The results suggest that pollution exchange coefﬁcient of Ben Beo are small, the basin may be at risk from water quality problems. The number of days required to achieve of 50% reduction in concentration for the mean tidal range: about 5 days using low and average values of b and 10 days using high value of b. The pollution flushing for maximum tidal range is strong. The number of days required to achieve a given percent dilution of the initial concentration is about 3 to 5 days for wide range of b values. However, model offers a reasonable approximation to heavy metal pollution. Keyword : Pollution exchange coefﬁcient, pollution flushing